BOARD RACE GAME AS AN ALTERNATIVE STRATEGY IN TEACHING VOCABULARY - Salmon J Hukom (Jurusan Pendidikan Bahasa dan Seni FKIP Universitas Pattimura, 2021)
Like other components of language in teaching, vocabulary needs special teaching strategy from teacher in order to make the students enrich the number of their vocabulary. This paper aims to discuss board race game as an alternative teaching strategy of vocabulary. Many experts and researchers have conducted studies about this game in teaching vocabulary and the results show significant improvement toward the enrichment of vocabulary after implementing board race game. The board race game has exciting steps in which they can encourage the students to become more active in teaching vocabulary. This game also presents new atmosphere in teaching and learning since it motivates the students to compete one another fairly